Identification of a novel bovine enterovirus possessing highly divergent amino acid sequences in capsid protein. Issue 1 (December 2017) - Tsuchiaka, Shinobu; Rahpaya, Sayed; Otomaru, Konosuke; Aoki, Hiroshi; Kishimoto, Mai; Naoi, Yuki; Omatsu, Tsutomu; Sano, Kaori; Okazaki-Terashima, Sachiko; Katayama, Yukie; Oba, Mami; Nagai, Makoto; et al.
Abstract Background Bovine enterovirus (BEV) belongs to the speciesEnterovirus E orF, genusEnterovirus and familyPicornaviridae . Although numerous studies have identified BEVs in the feces of cattle with diarrhea, the pathogenicity of BEVs remains unclear. Previously, we reported the detection of novel kobu-like virus in calf feces, by metagenomics analysis. In the present study, we identified a novel BEV in diarrheal feces collected for that survey. Complete genome sequences were determined by deep sequencing in feces. Secondary RNA structure analysis of the 5′ untranslated region (UTR), phylogenetic tree construction and pairwise identity analysis were conducted. Results The complete genome sequences of BEV were genetically distant from other EVs and the VP1 coding region contained novel and unique amino acid sequences. We named this strain as BEV AN12/Bos taurus /JPN/2014 (referred to as BEV-AN12). According to genome analysis, the genome length of this virus is 7414 nucleotides excluding the poly (A) tail and its genome consists of a 5′UTR, open reading frame encoding a single polyprotein, and 3′UTR. The results of secondary RNA structure analysis showed that in the 5′UTR, BEV-AN12 had an additional clover leaf structure and small stem loop structure, similarly to other BEVs. In pairwise identity analysis, BEV-AN12 showed high amino acid (aa) identities toEnterovirus F in the polyprotein, P2 and P3 regions (aa identity ≥82.4%). Therefore, BEV-AN12 is closely related toEnterovirus F . However, aa sequences in the capsid protein regions, particularly the VP1 encoding region, showed significantly low aa identity to other viruses in genusEnterovirus (VP1 aa identity ≤58.6%). In addition, BEV-AN12 branched separately fromEnterovirus E andF in phylogenetic trees based on the aa sequences of P1 and VP1, although it clustered withEnterovirus F in trees based on sequences in the P2 and P3 genome region. Conclusions We identified novel BEV possessing highly divergent aa sequences in the VP1 coding region in Japan. According to species definition, we proposed naming this strain as "Enterovirus K", which is a novel species within genusEnterovirus . Further genomic studies are needed to understand the pathogenicity of BEVs.